The Sexual and Racial Contradictions of Neoliberalism - Ferguson, Roderick A.; Hong, Grace Kyungwon (Journal of homosexuality, 2012)
In this article, the authors define neoliberalism as the current stage of racial capital that emerged after the worldwide liberation movements of the mid-twentieth century. The approach highlighted in this article observes neoliberalism's relationship to sexuality as one characterized by the accumulation of various racial projects, an accumulation that produces the political and economic conditions for inciting and regulating racialized gender and sexual formations. That is, the authors understand neoliberalism to denote the extension of recognition, validation, and legitimacy in ways that depend upon the simultaneous extension of exacerbated dispersals of death and devaluation. Adapted from the source document.